2005
DOI: 10.1021/jm040114b
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Paclitaxel (Taxol) Reduces P-Glycoprotein Interactions and Increases Permeation across the Blood−Brain Barrier in Vitro and in Situ

Abstract: The purpose of this work was to introduce a chemical modification into the paclitaxel (Taxol) structure to reduce interactions with the product of the multidrug resistant type 1 (MDR1) gene, P-glycoprotein (Pgp), resulting in improved blood-brain barrier (BBB) permeability. Specifically, a taxane analogue, Tx-67, with a succinate group added at the C10 position of Taxol, was synthesized and identified as such a candidate. In comparison studies, Tx-67 had no apparent interactions with Pgp, as demonstrated by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
63
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 26 publications
(76 reference statements)
1
63
0
1
Order By: Relevance
“…4,5 Paclitaxel's limited oral bioavailability, lack of accumulation in brain tissues, and efficacy in brain tumors has been attributed to active efflux by Pgp. 6,7 In our efforts to develop paclitaxel analogues that can cross the BBB, 8 we are studying the influence of chemical modifications of paclitaxel on Pgp in the BBB and are now reporting new results concerning structure-efflux relationships of paclitaxel analogues. A comparison of the structural features of over one hundred known substrates and modulators for Pgp suggested that clusters of hydrogen bond acceptors (electron donating groups), arranged in fixed spatial distances from each other, are required for recognition by Pgp binding sites.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 Paclitaxel's limited oral bioavailability, lack of accumulation in brain tissues, and efficacy in brain tumors has been attributed to active efflux by Pgp. 6,7 In our efforts to develop paclitaxel analogues that can cross the BBB, 8 we are studying the influence of chemical modifications of paclitaxel on Pgp in the BBB and are now reporting new results concerning structure-efflux relationships of paclitaxel analogues. A comparison of the structural features of over one hundred known substrates and modulators for Pgp suggested that clusters of hydrogen bond acceptors (electron donating groups), arranged in fixed spatial distances from each other, are required for recognition by Pgp binding sites.…”
mentioning
confidence: 99%
“…14 In another example, we have recently shown that Tx-67, a paclitaxel analogue, carrying a 10-O-succinyl monoester moiety, is able to evade Pgp-mediated efflux and can permeate the BBB in vitro and in situ. 8 Of interest in this context are also recent reports, disclosing that TXD-258 (7-O-methyl-10-O-methyldocetaxel) is able to cross the BBB, and that RPR-109881A (a 7,8-cyclopropyl docetaxel analogue) is effective against MDR-positive and taxane resistant human tumor xenografts. 15 Based on these previous observations, we decided to explore additional chemical modifications of the putative group 5 and 6 paclitaxel recognition elements with the goal to decrease the strength for Pgp binding and thereby improve activity against MDR cancer cells and enhance BBB permeation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Indeed, since Papp A-B values smaller than 3 cm 10 -6 /sec are predictive of low BBB-permeability, 22 it would appear that the MDR-MDCK model would not match the in vivo observation obtained for TX-67 in rat brain perfusion studies. 16 One possible explanation for this apparent discrepancy calls for the possible involvement of an active transporter (such as the carboxylic acid transporter) that might be responsible for the active uptake of TX-67 in vivo. 16 Additional studies are needed to investigate this possibility.…”
mentioning
confidence: 99%
“…16 One possible explanation for this apparent discrepancy calls for the possible involvement of an active transporter (such as the carboxylic acid transporter) that might be responsible for the active uptake of TX-67 in vivo. 16 Additional studies are needed to investigate this possibility. Comparative brain uptake studies (such as rat brain perfusion or brain/plasma ratio) between TX-67, CNDR-3 and CNDR-29, would provide important clues in support or against the possible involvement of a carboxylic acid transporter.…”
mentioning
confidence: 99%